Analysis of chlorophyll a concentration along the Galician coast: seasonal variability and trends - Alvarez, I. (2019)
The spatial and temporal distribution of chlorophyll a (Chl a) concentration was analysed along the Galician coast from 1998 to 2007. Sea surface temperature and Ekman transport data were also used to investigate the relationship between the ocean–atmosphere conditions and Chl a formation and variability. The west coast showed the highest Chl a concentration, with three peaks of maximum values (February, April–May, and July–September). Along the central coast, the pattern was similar, with the highest concentrations measured during spring and summer, but with lower values. The north coast was the least productive, with much lower values. The high seasonal variability of Chl a was mainly related to upwelling events during spring and summer. During autumn and winter, Chl a variations depended on other factors such as the input of nutrients from land run-off. There was no clear seasonal trend in Chl a.